Validity of the revision of the religious institutes’ constitutions, as well as their contents and form in light of church documents - SZEWCZUL, BOŻENA (Prawo Kanoniczne, 2017)
Basic norms of the religious institutes of the consecrated life, usually called constitutions, should comprise basic theological rules and law norms, which faithfully reflect institutes’ charisma and their spiritual patrimony. Each religious is obliged to faithfully preserve, develop and safeguard the patrimony of his own institute concerning its nature, purpose, character, spirit and sound traditions (Can. 578 CCL/1983). This way he will strive for perfect love of God by way of evangelical counsels following the method shown by founders inspired by the Holy Spirit. That’s why the faithful and communicative expressing of founders thoughts, and intentions in constitutions are so important. Constitutions are not simple book, which is put aside on the shelf, when it was already read, but must become real book of life for religious, and which contents they must constantly absorb, and implement into their own spiritual life and everyday activities. Therefore a manner of formulating the basic questions of constitution, and their language play very important role.